Effects of Sambiloto Ethanol Extract on Fatty Liver, SGOT/SGPT Levels and Lipid Profile of Wistar Strain White Rat (Rattus norvegicus) Exposed to High-Fat Diet - Jong, FX Himawan Haryanto; Gunawan, Ari; Santoso, Mochamad Wirono Aman; Anjani, Susilowati; Tirthaningsih, Ni Wayan; Basori, Ahmad (Folia Medica Indonesiana, 2018)
The aim of this study was to analyze the effects of ethanol extract of sambiloto (Andrographis paniculata) on fatty liver percentage, serum glutamic oxaloacetic transaminase (SGOT) level and lipid profile of wistar strain white rat exposed to high fat diet. The study used randomized post test only control group design. Total sample was 50 male wistar strain rats (Rattus norvegicus) divided randomly into 5 groups (randomization). The normality test used was Kolmogorov Smirnov test (a=0.05). The homogeneity test used was Levene test (a=0.05). The comparative test was done using Anova test (analysis of variance) (a=0.05) or Brown-Forsythe test (a=0.05). The correlation test was done using Pearson test (a=0.05). The administration of sambiloto ethanol extract with doses of 100, 200 and 400 milligrams (mg)/kilogram (kg) body weight (BW) decreased the percentage of fatty liver (r=-0.950), SGOT (r=-0.964)/SGPT (r=(R=-0.973)/LDL (low-density lipoprotein) (r=-0.960) and increased HDL (high-density lipoprotein) levels (r=-0.923)=0.956) in white rats exposed to a high-fat diet. In conclusion, increased dose of ethanol extract of sambiloto can decrease the percentage of fatty liver, SGOT/SGPT and total cholesterol/TG/LDL and increase HDL level of white rats exposed to high fat diet.